Transporter TAP1-637G and Immunoproteasome PSMB9-60H Variants Influence the Risk of Developing Vitiligo in the Saudi Population - Elhawary, Nasser Attia; Bogari, Neda; Jiffri, Essam Hussien; Rashad, Mona; Fatani, Abdulhamid; Tayeb, Mohammed (Disease Markers, 2014)
We evaluated whether TAP1-rs1135216 (p.637D>G) and PSMB9-rs17587 (p.60R>H) were significantly associated with the risk and severity of vitiligo among Saudi patients. One hundred seventy-two subjects were genotyped for the TAP1-rs1135216 and PSMB9-rs17587 variants using endonuclease digestions of amplified genomic DNA. The TAP1-rs1135216 and PSMB9-rs17587 mutant alleles were strongly associated with vitiligo, with odds ratios showing five fold and two fold risks (P<0.0001 and P=0.007, resp.). In TAP1-rs1135216, the 637G mutant allele was more frequent in cases (74%) than in healthy controls. In cases, the 60H mutant allele PSMB9-rs17587 was less frequent (42%) than the wild-type 60R allele (58%). Vitiligo vulgaris was the most common type of disease, associated with the DG (55%) and GG (46%) genotypes for rs1135216 and with the RH genotype (59%) for rs17587. The heterozygous 637DG and 60RH genotypes were each linked with active phenotypes in 64% of cases. In conclusion, the TAP1-rs1135216 and PSMB9-rs17587 variants are significantly associated with vitiligo, and even one copy of these mutant alleles can influence the risk among Saudis. Vitiligo vulgaris is associated with genotypes containing the mutant G and H alleles.